Millie lies low [videorecording (DVD)] - Savill, Michelle; Kent, Eli, 1988-; Scotney, Ana; House, Rachel; Alosio, Chris; Nguyen, Jillian; Cotton, Sam (Actor) (Film Movement series., 2023)
Millie, an architecture student from Wellington, New Zealand, has landed a competitive internship with a prestigious firm in New York. After telling everyone she knows about the opportunity, she suddenly suffers a panic attack as her plane is about to take off, and misses her flight. In a desperate pivot, Millie decides to save face by hiding in plain sight around Wellington, suitcase in tow, using Instagram and the power of denial to depict a trip to New York City that never happened.